Seeking Excellence in End of Life Care (SEE Care): A Multi-Centered Acute Hospitals Service Evaluation. (April 2022) - Tavabie, Simon; Berglund, Anja; Barclay, David; Bass, Steve; Collins, Naomi; Edwards, Elaine; Malik, Farida; Minton, Ollie; Peters, Deborah; Stewart, Eleanor; Winter, Jayne; Ford-Dunn, Suzanne
Context: A proportion of UK hospital inpatients have palliative care needs but do not access specialist services. Objectives: To contemporaneously evaluate the significance of unmet specialist palliative care needs within the hospital inpatient population. Methods: Prospective multi-centered service evaluation was conducted through 4 snapshots across 4 acute NHS hospital trusts. All patients identified as dying in each hospital were included. Data extraction included symptom burden, medications and completion of care plans. Results: End-of-life care plans were completed for 73%, symptom-focused prescribing present in 96%. Symptoms were not well managed for 22%, with 4% suffering moderate to severely. Specific intervention was triggered in 56% of patients, consisting of prescribing advice and holistic support. Conclusion: There are significant unmet specialist palliative care needs within the hospital inpatient population. Contemporaneous data collection coupled with an outreach approach helps palliative care services better understand the experiences of dying people, alongside where improvement is needed.